KONTRIBUSI KEARIFAN LOKAL DAN ETIKA BUDDHA DALAM PERSPEKTIF KEPEMIMPINAN MODERN - Mulyana Mulyana (Jurnal Pelita Dharma, 2014)
Centre  of Java have  various  local wisdom,  one of them related  to leadership sud:  as Sera/ W11la11g  Reh and Asta  Brnta Teaching.  Beside that, Budd/m's  Teaching  in text Jatnka  also concern  011  leadership,  called  Dasa  Raja Dhamma.  This article aim to study the  contribution   of local  wisdom,   specially  Serat W11la11g  Rel, and Asta   Brata Teaching mid  Buddhist   Ethics,  specially   Dasa  Raja  Dhamma   011  leadership  patten, iu modem  era. This research use the qualitatiue approach and libra,y research method